2019
DOI: 10.1186/s12931-019-0977-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pirfenidone on lung function decline and survival: 5-yr experience from a real-life IPF cohort from the Czech EMPIRE registry

Abstract: IntroductionPirfenidone, an antifibrotic drug, slows-down the disease progression in idiopathic pulmonary fibrosis (IPF) over 12 months, however limited data on the decline of lung function and overall survival (OS) in real-world cohorts on longer follow-up exists.Patients/methodsOf the enrolled Czech IPF patients (n = 841) from an EMPIRE registry, 383 (45.5%) received pirfenidone, 218 (25.9%) no-antifibrotic treatment and 240 (28.5%) were excluded (missing data, nintedanib treatment). The 2- and 5-yrs OS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 37 publications
5
75
1
2
Order By: Relevance
“…On the other hand, an observational study based on the Czech IPF registry showed substantial stability of FVC progression rate even after 2 years of therapy. 14 The latter discrepancy may be due to the progressive decrease in our sample size, which also included patients with severe lung volume impairment at baseline. At the same time, we cannot exclude that pirfenidone prevented an even more pronounced decline in FVC, as reported by the metanalysis of Nathan and colleagues 19 Moreover, the RECAP study, an open-label extension of the CAPACITY and ASCEND clinical trials, showed an annualized rate of FVC decline of 144 ± 6 ml over a follow up of 180 weeks, which was similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an observational study based on the Czech IPF registry showed substantial stability of FVC progression rate even after 2 years of therapy. 14 The latter discrepancy may be due to the progressive decrease in our sample size, which also included patients with severe lung volume impairment at baseline. At the same time, we cannot exclude that pirfenidone prevented an even more pronounced decline in FVC, as reported by the metanalysis of Nathan and colleagues 19 Moreover, the RECAP study, an open-label extension of the CAPACITY and ASCEND clinical trials, showed an annualized rate of FVC decline of 144 ± 6 ml over a follow up of 180 weeks, which was similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…That has led to the development of well-accepted diagnostic criteria for idiopathic pulmonary fibrosis (IPF), (1,2) as well as to the development of two drugs, pirfenidone and nintedanib, (3,4) which are able to slow the progression of the disease and may improve survival. This has been shown in different clinical registries from Australia, (5) Europe, (6,7) and the United States, (8) with an acceptable tolerance profile. In the same period, rare gene mutations associated with familial pulmonary fibrosis (FPF), involving surfactant-related genes (SFTPA1, SFTPA2, SFTPC, ABCA3, etc.)…”
Section: Amentioning
confidence: 74%
“…One reason could be the high mean age of 74 years in our patients. The mean ages of patients in the EMPIRE registry was 67 years [19], in the European IPF registry was 68 years [18], and in the AIPFR was 70.9 years [14]. However, to the best of our knowledge, this is the rst study from Japan and Asia.…”
Section: Discussionmentioning
confidence: 87%
“…The European IPF registry and AIPFR showed signi cantly longer survival in patients treated with anti brotics [14,18]. For speci c a drug, the EMPIRE registry showed that patients treated with pirfenidone exhibited signi cantly longer survival [19]. In a joint analysis of the phase 2 and 3 trials of nintedanib, the treatment group showed a signi cantly lower mortality rate than the placebo group [18].…”
Section: Discussionmentioning
confidence: 99%